Vague soft near-rings - Sushama Vijaykumar Patil; Janardan Dhyandev Yadav (Journal of Hyperstructures)
Soft set theory, proposed by Molodstov has been regarded as an effective mathematical tool to deal with uncertainties. Vague set is a set of objects, each of which has a grade of membership whose value is a continuous subinterval of [0,1]. Such a set is characterized by a truth membership function and a false membership function. In this paper we introduce and study the concept of vague soft near-rings, vague soft ideals of near-rings. Also, we derive some properties of vague soft near-rings and vague soft ideals of near-rings.